1980
DOI: 10.1111/j.1432-1033.1980.tb04310.x
|View full text |Cite
|
Sign up to set email alerts
|

Further Characterization of the Phosphate Moiety of the Adenovirus Type 2 DNA‐Binding Protein

Abstract: The adenovirus type 2 DNA‐binding protein is phosphorylated. Alkaline phosphatase treatment removes phosphate groups resulting in a decrease in molecular weight from 72000 to 70000. The dephosphorylated protein binds to single‐stranded and double‐stranded DNA as well as the phosphorylated protein does. Controlled chymotrypsin treatment cleaves the DNA‐binding protein into two subspecies of Mr about 45000 and 25000. The 45000‐Mr polypeptide contains most of the methionine residues but no phosphate and binds to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
0

Year Published

1981
1981
1998
1998

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 27 publications
(5 reference statements)
3
32
0
Order By: Relevance
“…It has been shown that the Ad 72000-M, DNA-binding protein is phosphorylated in viva [22] and in vitro [21,23,25]. In an attempt to characterize the kinase(s) involved, an Ad5-infected cell extract was prepared and the material was purified by affinity chromatography on DNA-cellulose and gel filtration through Ultrogel.…”
Section: Identification Of the Protein Kinase Activities Present In Pmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the Ad 72000-M, DNA-binding protein is phosphorylated in viva [22] and in vitro [21,23,25]. In an attempt to characterize the kinase(s) involved, an Ad5-infected cell extract was prepared and the material was purified by affinity chromatography on DNA-cellulose and gel filtration through Ultrogel.…”
Section: Identification Of the Protein Kinase Activities Present In Pmentioning
confidence: 99%
“…As isolated from infected cells, it is a phosphoprotein [21,22], but the influence of phosphorylation on its activity remains unclear.…”
mentioning
confidence: 99%
“…Mutations which affect the ability of the virus to grow in monkey cells appear to be confined to the N-terminal region (Anderson et al, 1983;Brough et al, 1985) whereas the functions relating to DNA replication and to DNA-and RNA-binding are located in the C-terminal domain (Ariga et al, 1980;Cleghon & Klessig, 1986;Seiberg et al, 1989). It has been suggested (Linne & Philipson, 1980;Klein et al, 1979) that these two domains can be separated by chymotrypsin treatment of the DBP; indeed some evidence of specific breakdown can be seen in extracts of infected cells. However the exact border of the domains is unknown with reported C-terminal fragments ranging from 34K to 45K.…”
Section: Introductionmentioning
confidence: 99%
“…In adenovirus type 2 (Ad2) and 5 this polypeptide, designated the DNA-binding protein (DBP), has an apparent Mr of 72K from analysis by SDS-PAGE, a value significantly higher than the value of 59K calculated from sequence data. Isoelectric focusing has resolved purified DBP into as many as 15 subspecies, of which at least some result from differing degrees of phosphorylation (Klein etal., 1979;Linne & Philipson, 1980). However Linne & Philipson (1980) showed that even after extensive treatment with bacterial alkaline phosphatase its apparent Mr was reduced by only 2K.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation